Islamic Coin sebagai Produk dari Kripto Syariah: Analisis Mekanisme dalam Perspektif Fikih Muamalah - Hana Widyadhana; Fahira Qolbu Muthmainah; Neida Haerunisa; Jaenudin J; Dian Herdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the mechanism of Islamic Coin as a sharia-compliant cryptocurrency developed to align with the principles of Islamic commercial jurisprudence (fiqh muamalah). The emergence of Islamic Coin responds to the growing interest of Muslim communities in halal digital assets and the need for modern financial instruments that uphold justice, transparency, and the avoidance of gharar, riba, and maysir. Using a qualitative approach and a case study method, this research analyzes the concept, operational structure, and sharia compliance level of Islamic Coin operating within the HAQQ Network. Core mechanisms such as the Shariah Oracle, the Proof of Stake model, and the allocation of social funds through the Evergreen DAO demonstrate efforts to establish a sharia-based digital ecosystem. However, challenges arise from limited adoption, lack of user experience, and the need for clearer contractual agreements to ensure that transactions are not merely labeled as â€œsharia-compliantâ€ but truly adhere to Islamic legal principles. The findings indicate that Islamic Coin holds potential as a halal and equitable digital financial instrument, though further enhancement in regulation, education, and mechanism transparency is required for broader acceptance among Muslim communities.